2021
DOI: 10.5670/oceanog.2021.123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Petroleum By-Products and Dispersants on Ecosystems

Abstract: Gulf of Mexico (GOM) ecosystems are interconnected by numerous physical and biological processes. After the Deepwater Horizon (DWH) disaster, these ecological processes facilitated dispersal of oil-spill toxicants or were damaged and broken. A considerable portion of post-DWH research focused on higher levels of biological organization (i.e., populations, communities, and ecosystems) spanning at least four environments (onshore, coastal, open ocean, and deep benthos). Damage wrought by the oil spill and mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
0
9
0
1
Order By: Relevance
“…Of the VOCs, about 0.14% are C 2 -C 6 hydrocarbons and 0.12% are C 1 -C 16 aldehydes/ ketones (organic compounds escaping complete combustion), 0.9% SO x and 0.0004% NO x (Figure 6a). Gullett et al (2017) performed laboratory-scale experiments by burning representative crude oil in two outdoor pans with areas of 0.47 m 2 and 0.93 m 2 . The pans were filled with seawater and a Strategic Petroleum Reserve Bayou Choctaw Sweet crude oil reported to have chemical composition and physical characteristics similar to that of the Macondo oil.…”
Section: In Situ Burning Of Oil At the Sea Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Of the VOCs, about 0.14% are C 2 -C 6 hydrocarbons and 0.12% are C 1 -C 16 aldehydes/ ketones (organic compounds escaping complete combustion), 0.9% SO x and 0.0004% NO x (Figure 6a). Gullett et al (2017) performed laboratory-scale experiments by burning representative crude oil in two outdoor pans with areas of 0.47 m 2 and 0.93 m 2 . The pans were filled with seawater and a Strategic Petroleum Reserve Bayou Choctaw Sweet crude oil reported to have chemical composition and physical characteristics similar to that of the Macondo oil.…”
Section: In Situ Burning Of Oil At the Sea Surfacementioning
confidence: 99%
“…Numerous studies have shown that PAHs from combustion sources contain more of the parent, non-alkylated PAHs compared to crude oils and fuel oils, with the predominance of the parent, non-alkylated PAHs increasing with higher temperatures of combustion (e.g., Lima et al, 2005). The composition of the PAHs associated with the soot and black carbon were assessed by several studies that measured mainly a number of parent PAHs in the molecular range of naphthalene through benzo [ghi] perylene (e.g., Gullett et al, 2016Gullett et al, , 2017. Insights into the general mechanisms of rapid molecular clustering that could lead from combustion-formed PAHs to black-carbon soot in general are provided by Johansson et al (2018).…”
Section: In Situ Burning Of Oil At the Sea Surfacementioning
confidence: 99%
“…These compounds included some of the chemicals, such as PAHs of concern for known or potentially adverse effects, as discussed in other papers in this issue (Rullkötter and Farrington. 2021;Murawski et al, 2021;Halanych et al, 2021).…”
Section: Important Factors To Consider Regarding the Relationship Between The Chemical Compositions Of Dwh Gas And Oil And Their Biogeochmentioning
confidence: 99%
“…We also describe novel approaches for investigating oil-induced physiological and ecological impacts on commercially and environmentally important fish and marine mammal species that help to provide a more comprehensive understanding of acute and sublethal effects on long-term population dynamics. Topics related to oil spill impacts on marine life are also discussed in Farrington et al (2021), Halanych et al (2021), Quigg et al (2021), Murawski et al (2021), andSandifer et al (2021), all in this issue. White et al (2012) combined the use of technologies that can operate in the deepsea environment with three-dimensional seismic data to find, image, identify, and collect samples of a damaged octocoral community 13 km southwest of the DWH site.…”
Section: Developments In Investigating Oil Spill Impacts On Marine Lifementioning
confidence: 99%
“…Emergent dispersant technologies as alternatives to Corexit that show promise as being effective and efficient in oil spill remediation and that are non-toxic to humans and the environment are considered below. Related topics are discussed in Quigg et al (2021) and Halanych et al (2021), both in this issue. Saha et al (2013) used surface-tunable carbon black (CB) particles as an alternative to Corexit for oil spill remediation.…”
Section: Emergent Dispersant Technologiesmentioning
confidence: 99%